Tarsocrural Arthrodesis: A Clinical Report Using a Circular External Fixator - Trostel, C. T.; Radasch, R. M. (Veterinary and Comparative Orthopaedics and Traumatology, 1998)
Arthrodesis is a well documented treatment option for comminuted intraarticular fractures, irreparable collateral ligament injuries, limb salvage for ischiatic nerve injury, and severe degenerative joint disease of the tarsocrural joint (1-6). Conservative splint or bandage application often results in a less than favorable outcome in the management of these types of injuries. Common techniques to achieve tarsocrural arthrodesis include divergent Steinmann pin placement, lag screw or compression plating and external skeletal fixation (1-5). This report describes a tarsocrural arthrodesis using a circular external fixation system to manage an open, severely contaminated, comminuted intra-articular fracture of the talus and calcaneous, with extensive soft tissue degloving injuries. The decision to use a circular external fixation system was based on its ability to (1) adequately stabilize the tibialtarsal region, (2) be applied with minimal soft tissue and vascular disruption, (3) allow adequate post-operative soft tissue wound management, and (4) be tolerated well by the patient allowing early weight bearing of the limb.Severe tarsocrural injuries were diagnosed on a four-year-old mixed breed dog including articular fractures of the tubercalcaneous, talus, fibula, multiple tarsal bones and the second metatarsal bone. A circular ring external fixator was used to arthrodese the joint. Twelve weeks following surgery the limb was functional without any mechanical gait alteration and with minimal to zero discomfort.
Keywords: Ilizarov’s ring fixator; circular fixator; tarsocrural arthrodesis